Outcomes of Dorsal and Ventral Buccal Graft Urethroplasty at a Tertiary Hospital in Uganda. (17th April 2014) - Kaggwa, S.; Galukande, M.; Dabanja, H.; Luweesi, H.
Abstract : Purpose . Although the use of buccal mucosa in substitution urethroplasty has been practiced for some years, it has not been free of controversy over which surgical technique is the most appropriate to use. There is paucity of data in Sub-Saharan Africa about its success; this study presents the outcomes of dorsal and ventral buccal graft urethroplasty at a sub-Saharan tertiary hospital. Methods . This is a prospective study in which buccal mucosa was used for ventral and dorsal grafts; followup was up to two years. All patients provided informed written consent for the procedures. Results . Seventy-two patients with bulbar urethral strictures underwent buccal graft one-stage urethroplasty. Mean age was 55 years; etiology of the strictures was postinflammatory due to urethritis from sexually transmitted infections 97% (70/72) and trauma 3% (2/72). Buccal mucosa grafts were harvested from the cheek using a two-team approach. Grafts were placed on the ventral and dorsal urethral surfaces in 32 and 40 cases, respectively; the success rate was 84 and 80%, respectively. Repeated urethroplasty was successfully done among 10% (7/72) and patients reported resolution of symptoms in the follow-up period. Conclusion . There was no difference between dorsal and ventral onlay buccal graft outcomes for bulbar urethral strictures. The success rate was 80 to 84%.